Seismic Performance of foundation with GEOGRID - Kandel, Samundra; Dangol, Bijaya; Khadka, Bishal; Bista, Janak; Karki, Jessica; Bishwokarma, Bibek (Journal of Nepal Geological Society, 2025)
This study investigates seismic performance analysis of geogrid stabilized foundations under numerical modeling using a Geotechnical Engineering Software, PLAXIS 2D. The research focuses on consecutive acceleration differences between floors to assess the effectiveness of geogrid in improving structural stability. The results of the study show that geogrid is effective in mitigating sudden change in acceleration from a floor to another, which leads to a homogeneous seismic response. Without geogrid, differences between consecutive floors were 0.049g (Basement–1st), 0.059g (1st–2nd), 0.032g (2nd–3rd), -0.023g (3rd–4th), and 0.053g (4th–5th). But with the addition of geogrid (1.8B width and 2m spacing case), corresponding differences were 0.017g, 0.025g, 0.034g, -0.007g, and 0.087g, respectively. The results indicate that the foundation stabilized by the geogrid experiences less abrupt change in acceleration floor to floor and thus performs less abrupt jumps that tend to cause more structural damage. For example, the basement-first-floor difference reduced by 65.3% and first-second-floor difference reduced by 57.6%, which is more smoothed seismic response. The study shows the benefits of inter-floor acceleration difference reduction, and general foundation stability enhancement by geogrid reinforcement. The study highlights the importance of geogrid-reinforced foundations in seismically active areas, and its findings helps in future structural design.